Associations between sleep quality and inflammatory markers in patients with schizophrenia. (30th December 2016) - Fang, Shih-Hua; Suzuki, Katsuhiko; Lim, Chin Leong; Chung, Ming-Shun; Ku, Po-Wen; Chen, Li-Jung
Abstract: Sleep disorder is a risk factor for several systemic inflammation-related diseases and there are extensive data showing that schizophrenia is associated with chronic low-grade systemic inflammation. This study investigated the associations between sleep quality and inflammatory markers in patients with schizophrenia, which has not been examined before. Sleep quality (total sleep time, sleep efficiency, sleep onset latency, total activity counts, wake after sleep onset, number of awakening, and average length of awakening) was measured using actigraphy in 199 schizophrenia inpatients. The state of inflammation was measured using blood concentration of white blood cells (WBC) and neutrophils, together with neutrophil–lymphocyte ratio (NLR), and platelet–lymphocyte ratio (PLR). The results showed that total sleep time was negatively associated with NLR and PLR, and sleep efficiency was negatively associated with neutrophil counts and NLR. Sleep onset latency, total activity counts, wake after sleep onset, and number of awakening were positively associated with WBC and neutrophil counts. The average length of awakening was positively associated with NLR and PLR. This is the first report to suggest that improving sleep quality may modulate the state of inflammation in patients with schizophrenia. Highlights: Total sleep time was negatively associated with neutrophil–lymphocyte ratio and platelet–lymphocyte ratio, and sleep efficiency was negatively associated with neutrophil counts and neutrophil–lymphocyte ratio. Higher sleep onset latency, sleep activity counts, number of awakening and wake after sleep onset, which compromise sleep quality, were positively associated with the inflammatory markers of WBC and neutrophil counts. Improving sleep quality in patients with schizophrenia may modulate the state of inflammatory in patients with schizophrenia.